PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP PENGHINDARAN PAJAK DENGAN RASIO CAKUPAN PEMERIKSAAN PAJAK SEBAGAI VARIABEL MODERASI - Boli, Hubertus Ade Resha Raditya; Lestari, Sabrina Deby (STIE Madani Balikpapan, 2025)
This study examines the impact of Good Corporate Governance (GCG) on Tax Avoidance, with the Tax Audit Coverage Ratio as a moderating variable. GCG is measured using three proxies: Managerial Ownership, Independent Commissioners, and Audit Committee. This quantitative research utilizes secondary data from 42 publicly listed companies on the Indonesia Stock Exchange (2019–2023). The study employs purposive sampling and multiple linear regression analysis using SPSS. Findings reveal that Managerial Ownership reduces Tax Avoidance, Independent Commissioners have no significant effect, and Audit Committee increases Tax Avoidance. Additionally, the Tax Audit Coverage Ratio strengthens the negative influence of Managerial Ownership on Tax Avoidance. However, it does not moderate the relationship between Independent Commissioners or Audit Committee and Tax Avoidance.